Ferrofluid synthesis using oleic acid coated Fe3O4 nanoparticles dispersed in mineral oil for heat transfer applications. (28th March 2018) - Imran, Mohd; Ansari, Akhalakur Rahman; Shaik, Aabid Hussain; Abdulaziz,; Hussain, Shahir; Khan, Afzal; Chandan, Mohammed Rehaan
Abstract: Ferrofluids are stable dispersion of iron oxide nanoparticles in a carrier fluid which find potential applications in heat transfer. Fe3 O4 nanoparticles of mean size in the range of 5–10 nm were synthesized using conventional co-precipitation method. This work deals with the synthesis of ferrofluids using mineral oil as a carrier fluid and oleic acid coated Fe3 O4 nanoparticles as dispersed phase. Morphology (shape and size) and crystallinity of the synthesized nanoparticle is captured using TEM and XRD. Oleic acid coating on nanoparticle is probed using FTIR for confirming the stability of ferrofluid. Thermal properties of mineral oil based ferrofluid with varying concentration of nanoparticles are evaluated in terms of thermal conductivity. It was found that the thermal conductivity of ferrofluid increases upto 2.5% (w/v) nanoparticle loading, where a maximum enhancement of ∼51% in thermal conductivity was recorded as compared to the base fluid.